2015
DOI: 10.17305/bjbms.2015.207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Conventional Imaging Techniques on Preoperative Localization in Primary Hyperparathyroidism

Abstract: We aimed to evaluate the diagnostic and preoperative localization capacity of 99mTc methoxyisobutylnitrile (MIBI) parathyroid scintigraphy and ultrasonography (USG) in enlarged parathyroid glands in the primary hyperparathyroidism (pHPT) as well as the relationship between the success rate of these techniques and biochemical values. In this study, we retrospectively evaluated 39 patients with clinical and biological evidence of pHPT who referred to the university hospital for MIBI parathyroid scintigraphy. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…In 99mTc-MIBI imaging, this decrease in sensitivity might be associated with a delay in washout in multinodular goiter and Hashimoto's thyroiditis, whereas in USG, this decrease might be associated with the limitation of sonographic evaluation of adenoma because of a multinodular thyroid gland. However, it has been reported that benign and malign thyroid diseases might cause false positive results [22][23][24]. In our study, 33% of patients had concomitant thyroid disease.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In 99mTc-MIBI imaging, this decrease in sensitivity might be associated with a delay in washout in multinodular goiter and Hashimoto's thyroiditis, whereas in USG, this decrease might be associated with the limitation of sonographic evaluation of adenoma because of a multinodular thyroid gland. However, it has been reported that benign and malign thyroid diseases might cause false positive results [22][23][24]. In our study, 33% of patients had concomitant thyroid disease.…”
Section: Discussionmentioning
confidence: 44%
“…There is concomitant thyroid pathology in 20-30% of patients with primary hyperparathyroidism [21]. The presence of thyroid pathology decreases the sensitivity of both USG and 99mTc-MIBI imaging [22][23][24]. In 99mTc-MIBI imaging, this decrease in sensitivity might be associated with a delay in washout in multinodular goiter and Hashimoto's thyroiditis, whereas in USG, this decrease might be associated with the limitation of sonographic evaluation of adenoma because of a multinodular thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is an association between the utility of either USG or MIBI and the weight of a parathyroid adenoma [37]. However, Ozkaya et al showed that correct identification of pathology is provided in 90.9% of cases while applying MIBI, and 87.1% with USG in patients with a single parathyroid adenoma [39]. Other studies shown the accuracy of preoperative localization of parathyroid adenomas using USG is higher (93%) comparing to MIBI (90%); the researchers have also showed that USG has higher sensitivity (98%) than MIBI (93%) [40].…”
Section: Preoperative Imaging Techniques-ultrasonography Computed Tomentioning
confidence: 99%
“…Reaching such high diagnostic precision allows minimization of the extent of surgical procedure and gives way to applying routinely and successfully minimally invasive parathyroidectomy of the pathologically changed glands. 28 Ozkaya et al 29 evaluated the diagnostic and preoperative localization capacity of 99m Tc-sestamibi scintigraphy and US in patients with PHPT. They concluded that the overall sensitivities of 99m Tc-sestamibi scintigraphy, US and combined techniques were 85.3%, 72,5% and 90.4%, respectively.…”
Section: Parathyroid Scintigraphy With 99m Tc -Sestamibimentioning
confidence: 99%